The Effect of Cafe Atmosphere on Loyalty through Customer Satisfaction - Rina Mudjiyanti; Maratus Sholihah (Innovation Business Management and Accounting Journal, 2022)
The lifestyle of people who like to go out for coffee has made many people open businesses. With the products or prices offered not much different, this makes it difficult for business owners to get loyal customers because of the many competitors. The atmosphere can be an alternative to distinguish one cafe from another. This study aims to determine the effect of atmosphere on consumer satisfaction and loyalty, and to determine the effect of cafe atmosphere on loyalty through customer satisfaction. This study uses a quantitative approach, where research focuses on measuring and analyzing cause-and-effect relationships between several variables. The research sample used was 100 cafe customers and data were obtained through distributing questionnaires. Data analysis using PLS obtained the results that the atmosphere has an effect on consumer satisfaction. Atmosphere also affects consumer loyalty. The unique finding of this research is that the cafe atmosphere affects loyalty through customer satisfaction.